How does Financial Stability Affect Renewable Energy Investment? - Alsagr, Naif; Belkhaoui , Samir; Sohail, Sidra; Ozturk, Ilhan (International Journal of Energy Economics and Policy, 2025)
There is no doubt that financial stability is crucial for the sustainable economic growth of a nation. Nevertheless, whether it has any role in aiding renewable energy investment is an empirical question that has not received much consideration in the past. Therefore, our primary goal is to examine the role of financial stability in promoting renewable energy investment in top-polluting economies from different regions of Asia, Africa, America, and Europe. To that end, our selected estimation technique is CS-ARDL. Our long-run results reveal that financial stability and GDP cause renewable energy investment to rise in all regions except Africa. On the other hand, carbon emissions and ICT favorably influence renewable energy investment in all regions. The short-run estimates are insignificant in most instances. Since financial stability is crucial for promoting renewable energy investment, policymakers must focus on a more stable financial sector, and financial stability should be part and parcel of any policy design to promote renewable energy investment.